The Interaction of Lexical Ambiguity and Irony in Barbie (2023): A Semantic–Pragmatic Study of Meaning Construction in Film Dialogue - Belgis Raya Bian Paradieshta; Buyun Khulel (CAKRAWALA LINGUISTA, 2026)
This study investigates how lexical ambiguity and irony contribute to meaning construction in the dialogue of Barbie (2023). It aims to identify selected forms of lexical ambiguity, describe the types of irony used in the film, and explain how both linguistic devices construct social criticism related to gender, identity, and power. The study employed a qualitative descriptive design supported by directed qualitative content analysis. The data consisted of selected English dialogue exchanges from the film, verified through the screenplay and subtitles. The data were analyzed using a semantic–pragmatic approach through identification, classification, contextual interpretation, and coding in a data matrix. The findings show that lexical ambiguity is primarily represented through polysemy and literal–figurative extension, particularly in expressions such as perfect, real, dying, and played with. Meanwhile, verbal, situational, and dramatic irony are used to reveal contradictions in beauty ideals, gender roles, corporate empowerment, and masculine entitlement. The analysis also indicates that expressions such as ordinary, Dreamhouse, and box function mainly as evaluative or symbolic re-framing within ironic contexts rather than as direct cases of lexical ambiguity. Overall, the findings demonstrate that the dialogue in Barbie functions not only to create humor and support narrative development, but also to question fixed assumptions about femininity, identity, social power, and institutional control.